Transforming Arabic Language Learning Through Digital Pedagogy: Integrating Web-Based Media in the Society 5.0 Era - Muhammad Lanri Siregar; Ahmad Masruri (Al-Qalam Institue, 2026)
This study aims to analyze the digital pedagogical strategies employed by Arabic language teachers in integrating web-based media to support learning in the Society 5.0 era. A qualitative library research approach was adopted by reviewing relevant scientific journal articles, books, and scholarly documents. The collected data were analyzed using content analysis to identify key patterns and strategies in digital pedagogy for Arabic language learning. The findings reveal three major strategies: (1) the implementation of Blended Learning and Flipped Classroom models to promote flexible and student-centered learning; (2) the integration of interactive web-based media, such as Kahoot, Quizizz, Wordwall, and online language learning platforms, to enhance learner engagement and participation; and (3) the application of digital assessments that emphasize Higher Order Thinking Skills (HOTS). These strategies contribute to improving learning effectiveness, increasing student motivation, and fostering digital competencies alongside Arabic language proficiency. The study implies that strengthening teachers' digital literacy and expanding technological infrastructure are essential to achieving effective and sustainable Arabic language learning in the Society 5.0 era.